Ice sheet instability and meltwater events along the Svalbard–Barents Sea margin during the last 60,000 years - R.G. Lucchi; C. Caricchi; L. Sagnotti; M.E. Musco; G. Giorgetti; R. Ventrice; N. Douss; F. Princivalle; C. Morigi; P. Macrì; F.S. Gois Smith; A. Caburlotto; et al. (Global and Planetary Change, 2026)

Climate change adaptation mainstreaming through strategic environmental assessments. An in-depth analysis of environmental indicators from spatial plans in Friuli Venezia Giulia Region (Italy) - M. Granceri Bradaschia; D. Longato; D. Maragno; F. Musco (Environmental Impact Assessment Review, 2024)

Anchovy (Engraulis encrasicolus) early life stages in the Central Mediterranean Sea: connectivity issues emerging among adjacent sub-areas across the Strait of Sicily - B. Patti; R. Zarrad; O. Jarboui; A. Cuttitta; G. Basilone; S. Aronica; F. Placenti; G. Tranchida; G. M. Armeri; G. Buffa; R. Ferreri; S. Genovese; et al. (Hydrobiologia, 2018)

A Mediterranean record of Eulalia ornata (Annelida: Phyllodocidae) corroborating its fidelity link with the Sabellaria alveolata-reef habitat - E. SCHIMMENTI; L. MUSCO; S. LO BRUTTO; B. MIKAC; A. NYGREN; F. BADALAMENTI (Mediterranean Marine Science, 2015)
Among marine habitats Sabellaria alveolata-reefs deserve protection since they provide important ecosystem services and positive effects on biodiversity. Several marine species are listed among the S. alveolata-reef associated fauna, but characteristic species were seldom reported. Eulalia ornata (Annelida, Phyllodocidae) might represent an exception, since it appears common/abundant in S. alveolata-reefs of the Eastern Atlantic. The most evident geographical mismatch in the distributions of E. ornata and these biogenic reefs occurs in the Mediterranean Sea, where S. alveolata-reefs are commonly found, but E. ornata was never recorded, whilst E. viridis, a non-Mediterranean species, was previously listed among the dominant reef-associated taxa. The faunal characterization of the sabellarid reefs along the Sicily Channel revealed an Eulalia species as the dominant taxon associated with that habitat in the area. A taxonomic approach integrated with DNA barcoding, and comparisons with closely related species, allow us to report E. ornata as a new record for the Mediterranean Sea. We describe patterns of abundance and distribution and corroborate its status as a preferential species in the S. alveolata-reef habitat. Focusing on the biology and ecology of E. ornata could help us to better understand the dynamics and functioning of this valuable European shallow marine habitat.

Concern about the spread of the invader seaweed Caulerpa taxifolia var. distichophylla (Chlorophyta: Caulerpales) towards the West Mediterranean - L. MUSCO; F. ANDALORO; B. MIKAC; S. MIRTO; T. VEGA FERNADEZ; F. BADALAMENTI (Mediterranean Marine Science, 2014)
The new Australian alien seaweed Caulerpa taxifolia var. distichophylla, after being established along the Turkish Mediterranean coast in 2006, was recorded in Southern Sicily in 2007. Since then local fishermen claimed support to counteract the effects of entanglement of large amounts of the alien strain wrack in their trammel nets, causing the gear to become ineffective. The further northward and westward spread of the new alien strain is supposed to be limited by winter temperature. We present novel data confirming that the new alien strain is fully naturalized in Central Mediterranean and is expanding its range beyond such limit (i.e. the 15°C February isotherm), thus becoming potentially able to colonize the western basin. By means of a preliminary estimation of effects on native polychaete assemblages, and considering some peculiarities of Sicily (mostly linked to its geographical position in the Mediterranean Sea), the risk linked to the increasing range of distribution of the invasive algae is highlighted.